Результати експериментальних досліджень впливу епіламних покриттів на знос деталей шестеренного насосу - В’юник, Ольга Володимирівна; Вьюник, Ольга Владимировна; Viunyk, Olha; Дідур, В. В.; Сєрий, Ігор Сергійович; Серый, Игорь Сергеевич; Sieryi, Ihor (ТДАТУ, 2020)
UK: Питання підвищення ефективності використання мобільних машин, оснащених гідравлічними системами – важливе питання сьогодення. Ефективність роботи сільськогосподарської техніки залежить, від її надійності. Основним показником, що визначає працездатність і ресурс техніки є інтенсивність зношування деталей тертя. Одним з методів підвищення довговічності трібоспряжень мобільної сільськогосподарської техніки є застосування фінішної антифрикційної безабразивної обробки. В статті представлено гідравлічну принципову схему стенду на якому проводились експериментальні дослідження. Описано порядок проведення стендових випробувань, надано результати експериментальних досліджень. Результати проведених експериментальних досліджень підтверджують ефективність застосування поверхнево-активних речовин з метою збільшення післяремонтного ресурсу шестеренних насосів. Сегодня вопрос повышения эффективности использования мобильных машин, оснащенных гидравлическими системами стоит очень остро. Основным показателем, определяющим работоспособность и ресурс техники является интенсивность износа деталей трения. Правильно выбрав материал и покрытие трибосопряжений, можно значительно повысить износостойкость и долговечность узлов трения при эксплуатации. RU: В статье представлена гидравлическая принципиальная схема стенда на котором проводились экспериментальные исследования. Описан порядок проведения стендовых испытаний гидронасосов, предоставлены результаты экспериментальных исследований. Результаты анализа полученных зависимостей подтверждают эффективность применения поверхностно-активных веществ с целью увеличения послеремонтного ресурса шестеренных насосов. EN: The issue of improving the efficiency of mobile machines equipped with hydraulic systems is an important issue of today. The efficiency of agricultural machinery is mainly dependent on its reliability, namely the ability to perform specified functions with minimal use of labor and material resources for extended periods of time. The mainindicator that determines the efficiency and resources of equipment is the intensity of wear on the friction parts. Operating experience shows that up to 90% of machine parts fail due to wear. By choosing the right material and coating of the tribocouplings, you can significantly increase the wear resistance and durability of the friction units duringoperation. The most promising and economical way to increase the efficiency and resource of friction units of mobile agricultural machines is to optimize the choice of coatings for parts of the tribocoupling. One of the methods of increasing durability of the tribocouplings of the mobile agricultural machinery is the use of an antifriction nonabrasive finishing treatment. This work is a part of the research on improving the postrepair durability of friction units of gear pumps by reducing wear of parts during the runin period. The article presents a hydraulic schematic diagram of the stand КИ-4815М on which experimental studies were conducted. The order of bench tests of hydraulic pumps is described, the results of experimental research on receiving functional dependence of structural parameters of a technical condition of the details treated by epilam from functional parameters and a hydraulic pump operating time are given. The analysis of the received dependences is carried out. The results of experimental studies shows that the use in the technological process of the repair of gear pumps modification НШ-К, operations of treatment of parts of the pumping unit by epilam "Polysam-05" confirms the effectiveness of surfactants to increase the post-repair lifespan of gear pumps.
Результаты экспериментальных исследований влияния эпиламных покрытий на износ деталей шестеренного насоса
The results of txperimental studies the effect of eplam coatings on the wear of the gear pump parts
Keywords: техніка; шестеренний насос; дослідження; експеримент; поверхнево-активні речовини; вузол тертя; залежність; методика; шестеренчатый насос; исследование; эксперимент; поверхностно-активные вещества; узел трения; зависимость; technique; gear pump; research; experiment; surfactants; triboconjugation; dependence